KEGIATAN PENYULUHAN TENTANG REMATIK PADA LANSIA DI WILAYAH KERJA PUSKESMAS NGARAS KABUPATEN PESISIR BARAT - Umi Romayati Keswara; Dewi Kusumaningsih; Wahid Tri Wahyudi; Rahmat Hidayat (JURNAL KREATIVITAS PENGABDIAN KEPADA MASYARAKAT (PKM), 2018)
ABSTRACT Rheumatism, stiff, muscle and joint pain, are common illnesses in our lives. And mostly in elder people who are close to rheumatic disorders which is one of the degenerative diseases. The objective of the activity is increasing knowledge of participants about rheumatic care. This activity was done at Monday, December 18, 2017. The education was done using poster and leaflets. The result of education  showed  an increase knowledge in elder people is about 70%. Recommended that elderly participants can perform rheumatic disease treatment by avoiding trigger factors and performing rheumatic exercises. Keywords: Rheumatism, Elderly, Care.